Aortic root to left atrium fistula: a rare complication of infective endocarditis in a native aortic valve - Pereira, Vitor H. (2014)
The image shows a pseudoaneurysm of the mitral-aortic intervalvular fibrosa and a fistula between the non-coronary sinus and the left atrium.